A psychometric study: The validation of a school quality assessment tool - H. Berbar; S. Lotfi; M. Essaoudi; M. Talbi (Russian State Vocational Pedagogical University, 2022)
Introduction. School evaluation is a complex process, and it is now a central priority for education systems with varied practices and multiple actors. It affects many aspects: teachers, institutions, training, management, educational policies, and design. Thus, it is necessary to think first about the regulation of the indicators that will serve as a system of valuation/sanction of the quality measured.Aim. The present research aims to construct a grid for evaluating pedagogical and administrative quality of secondary school. Furthermore, producing a quality evaluation system based on indicators to allow quality to be witnessed remains a challenge. We have optimized and validated a coherent evaluation system of indicators (School Quality Assessment System SEQES). It is based on rigorous scientific research, evaluating school quality and testing with 196 stakeholders (school administrators, teachers, educational inspectors, and planning).Research methodology and methods. The design and validation of this evaluation grid were carried out based on Churchill's (1979) theory of measurement with a methodological process of numerous steps of analysis and emergent categorisation of items, scaling, refinement, and field testing.Results and scientific novelty. The exploratory factor analysis (EFA) was administered to 196 stakeholders and initially yielded 153 items from 289. They articulated qualitative steps (interviews with members of audit cells, techniques: Focus Group, TGN, TRIAGE) and quantitative (Exploratory Factor Analysis). The results made it possible to identify a scale of seven dimensions and fields of 37 items, considering theoretical, empirical, and methodological considerations.Practical significance. This measurement instrument is a toolbox that can be developed for decision-makers to establish a reference system for systematic external quality evaluation at the national level and a toolkit for inspectors and headteachers.